Improving Passivation Process of Si Nanocrystals Embedded in SiO2 Using Metal Ion Implantation - Jhovani Bornacelli; Jorge Alejandro Reyes Esqueda; Luis Rodríguez Fernández; Alicia Oliver (Journal of Nanotechnology)
We studied the photoluminescence (PL) of Si nanocrystals (Si-NCs) embedded in SiO2 obtained by ion implantation at MeV energy. The Si-NCs are formed at high depth (1-2 μm) inside the SiO2 achieving a robust and better protected system. After metal ion implantation (Ag or Au), and a subsequent thermal annealing at 600°C under hydrogen-containing atmosphere, the PL signal exhibits a noticeable increase. The ion metal implantation was done at energies such that its distribution inside the silica does not overlap with the previously implanted Si ion . Under proper annealing Ag or Au nanoparticles (NPs) could be nucleated, and the PL signal from Si-NCs could increase due to plasmonic interactions. However, the ion-metal-implantation-induced damage can enhance the amount of hydrogen, or nitrogen, that diffuses into the SiO2 matrix. As a result, the surface defects on Si-NCs can be better passivated, and consequently, the PL of the system is intensified. We have selected different atmospheres (air, H2/N2 and Ar) to study the relevance of these annealing gases on the final PL from Si-NCs after metal ion implantation. Studies of PL and time-resolved PL indicate that passivation process of surface defects on Si-NCs is more effective when it is assisted by ion metal implantation.